Prevalence of psychotropic substance use by urban bus drivers: a systematic review - Barbosa, Luciano Augusto da Silva; Andrade, André Luiz Monezi; Oliveira, Lúcio Garcia de; Micheli, Denise De (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2018)
Objective: to investigate the prevalence of psychotropic substance use by urban bus drivers by reviewing studies addressing drug use among this population and identify potential associations between drug use and sociodemographic and occupational variables inherent to the profession. Method: systematic literature review searching the MEDLINE, LILACS, SciELO, EMBASE, PsycINFO and CAPES databases using the Portuguese equivalents of the following: bus drivers, urban bus drivers, and drug use from July to December 2015. Results: these professionals are exposed to important occupational stressors daily and the consumption of drugs may be related to negative coping strategies. Drug use among these workers is of concern, as well as the apparent relationship between drug use and traffic accidents. Conclusion: stressors inherent to the profession and inefficacious responses to stress may lead these professionals to use psychotropic substances. Thus, studies addressing the prevalence of drug use in a significant sample of urban bus drivers are necessary.